Risk Management Based on Model of Competences when Introducing Innovative Information Technology - A. Bogatenkov, S.; A. Belevitin, V.; L. Khasanova, M. (International Journal of Engineering and Technology, 2018)
Economic expediency and attractiveness of life quality improving are accompanied by risks of increasing instability and possible collapse of the world system. Forecasts of the labour market change connected with automation of working places and mass unemployment cause concerns. The task of risk management in the personnel training system for introduction of new information technology is considered. The purpose of the research is development of the methodology based on the models of competences including requirements for safe application of information-measuring systems, as well as for an education level, work experience and permit-to-work documents in new conditions. A complex of new mathematical models, methods and technologies providing safety of the process of information technology introduction owing to the systemic approach to risk minimization is taken as a basis of the methodology. Invariant models provide economic effectiveness of processes of designing the system of safety and planning of educational paths. Models of personal paths of development and classes of competences provide didactic safety. Decision-making methods provide information, psychological, social and economic safety of the process of information technology introduction. The methodology is realised when introducing distance learning technologies in educational organisations of Chelyabinsk and the Chelyabinsk region.Â Â